A STUDY OF SCIENCE STUDENTS' MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE (EFL) AT THE DARUL HIKMAH LANGUAGE DORMITORY - Yulianti, Erma; Suryanto, Bradhiansyah Tri (Premise: Journal of English Education and Applied Linguistics, 2024)
Motivation is an essential factor in teaching and learning activities. English is learned as a foreign language and is essential in every aspect, especially education. The researcher explored this study because he saw the enthusiasm of science students toward English. The purpose of this research is to find out what motivation the students majoring in science have. This research uses a descriptive qualitative design. In this study, the researcher examined two 32 students majoring in IPA MAN 1 Probolinggo d in learning English as a foreign language at the Darul Hikmah language dormitory: extrinsic motivation Data were collected through observation and interviews with ten questions to the participants. The researcher analyzed the data using the thematic analysis method. Based on the findings, the results of this study show that students have good extrinsic and intrinsic motivation. The extrinsic motivation possessed by students in this study is encouragement from parents, the desire to get a good job, and motivation from students of Darul Hikmah Islamic Boarding School who interact using English. For students, intrinsic motivation is the desire to interact fluently using English and open private lessons. In addition, the interview results show that the teacher's role also influences the students' learning process.